Determinants of exclusive breastfeeding among mothers of infants aged 6 to 12 months in Gwanda District, Zimbabwe - Paddington T. Mundagowa; Elizabeth M. Chadambuka; Pugie T. Chimberengwa; Fadzai Mukora-Mutseyekwa (International Breastfeeding Journal, 2019)
Abstract Background In 2016, 98% of children in Zimbabwe received breastmilk, however only 40% of babies under six months were exclusively breastfed 24 h prior to data collection. A 2014 survey revealed that Matabeleland South Province had the country’s highest starvation rates and food insecurities were rife. This study aimed at investigating maternal, infant, household, environmental and cultural factors influencing exclusive breastfeeding (EBF) practice in Gwanda District. Methods A cross-sectional study was conducted from January to March 2018. Interviews used pretested structured questionnaires for 225 mothers of infants aged between six and twelve months at immunization outreach points and health facilities. Descriptive statistics, bivariate and multivariate analysis estimated the association between the dependent and independent variables. Exclusive breastfeeding was defined as feeding an infant on breast milk only from birth up to the age of six months. Results The majority of mothers (n = 193; 89%) had knowledge about EBF and 189 (84%) expressed a positive attitude towards the practice, however, only 81 (36%) practiced exclusive breastfeeding. The most common complementary food/fluid given to the infants was plain water (n = 85; 59%). Predictors for EBF were: maternal Human Immuno-deficiency Virus positive status (Odds Ratio [OR] 0.30; 95% Confidence Interval [CI] 0.17, 0.56) and being economically independent (OR 0.41; 95% CI 0.21, 0.79). Barriers to practicing EBF were: being a young mother under 25 years of age (OR 3.05; 95% CI 1.67, 5.57), having one or two children (OR 2.49; 95% CI 1.29, 4.79), living in less than two rooms (OR 3.86; 95% CI 1.88, 7.93) and having a baby of low birthweight (OR 1.05; 95% CI 0.40, 2.71). After multivariate analysis, only the mother’s economic independence was associated with practicing EBF (Adjusted OR [AOR] 0.83; 95% CI 0.30, 0.92). Key informants identified traditional family practices as the major barrier to EBF. Conclusion The exclusive breastfeeding rates were low despite the mothers’ high knowledge levels and positive attitudes towards the practice. In addressing the multiple factors influencing the cost effective practice, there is need to channel supportive measures through a system-wide approach. This can be achieved by realigning breastfeeding policy directives as well as community attitudes and values towards the exclusive breastfeeding.